Artisanal food of animal origin as reservoir of putative pathogenic Escherichia coli: a combined genomic and in vivo approach - Pasquali, Frédérique; Crippa, Cecilia; Lucchi, Alex; Manfreda, Gerardo (Frontiers in Microbiology, 2026)
The lack of a full automation and control of environmental parameters might result in potential risk of microbial contamination in small-scale production plants such as artisanal cheese and salami Italian productions. In a previous study, genomes of 33 E. coli isolates were sequenced. In the present study, the pathogenicity potential of E. coli strains was investigated by: (1) phylogenomic comparison with 202 public genomes of human, animal and environmental Italian origin; (2) pathogenicity assessment of strains with virulence patterns predicting specific E. coli pathotypes by using larvae of Galleria mellonella as in vivo infection model. Phylogenetic reconstruction revealed raw material and not the processing environment as source of salami contamination. Moreover, close proximity of some strains isolated from salami production with wild boar and extraintestinal human public strains was observed suggesting pigs and wild boar as potential reservoirs of pathogenic E. coli. The virulome of salami strains revealed the presence of genes already described as gene markers of atypical enteropathogenic E. coli (aEPEC; bfp-, eae+). Interestingly the analysis of virulence genes pointed toward additional genomes which showed genetic markers previously described as strongly associated to and/or extraintestinal pathogenic E. coli (ExPEC). In vivo experiments, confirmed the higher pathogenicity of strain 5STM5 with genetic pattern corresponding to hybrid aEPEC/ExPEC and two strains 3CP1522 and 6MB5 of cheese and salami production, respectively, with virulence genes previously associated to ExPEC pathotype. The combined approach pointed toward two genes espC for aEPEC, as well as malX for ExPEC which were significantly enriched in clinical genomes in comparison to genomes of other origins. These genes are worth of future investigations which could help to assess the risk for consumers after the consumption of contaminated artisanal food.